DINAMIKA PEMBENTUKAN KOMUNITAS DIGITAL DAN IDENTITAS VIRTUAL DI ERA MEDIA SOSIAL - Karina Azahra Putri; Sardin; Nindita Fajria Utami (Lembaga Sepercenter, 2025)
This study aims to analyze the dynamics of the formation of digital communities and virtual identities in the context of social media. The background of this study is the widespread use of social media that encourages the birth of digital communities based on shared interests, which contribute to the construction of virtual identities of its users. The research method uses a qualitative approach through in-depth interviews, observations, and documentation of participants who are active in digital communities in the city of Bandung. The results of the study show that digital communities are formed on the basis of shared interests, facilitating intensive interactions that allow individuals to build virtual identities through digital symbols, adjustments to community norms, and adaptation strategies to social dynamics such as fanwars or differences of opinion. The virtual identities that are formed are more flexible, bold, and often different from identities in the real world. The conclusion of this study is that digital communities play an important role in the formation of dynamic virtual identities, as a reflection of the ever-evolving digital social interactions.